51.7k views
0 votes
The sum of the ages of two brothers is 22 years.Six years ago the product of their ages was 21 years find the age of the elder brother

User TheDiveO
by
5.4k points

1 Answer

4 votes

Explanation:

x = age of brother 1 today

y = she of brother 2 today

x + y = 22

(x - 6)(y - 6) = 21

as 6 years ago, both were 6 years younger. than today.

from the first equation we get e.g.

x = 22 - y

using that in the second equation we get

(22 - y - 6)(y - 6) = 21

(16 - y)(y - 6) = 21

16y - 96 - y² + 6y = 21

-y² + 22y - 117 = 0

the general solution to a quadratic equation is

x = (-b ± sqrt(b² - 4ac))/(2a)

in our case

x = y

a = -1

b = 22

c = -117

y = (-22 ± sqrt(22² - 4×-1×-117))/(2×-1) =

= (-22 ± sqrt(16))/-2 = (-22 ± 4)/-2

y1 = (-22 + 4)/-2 = 9

y2 = (-22 - 4)/-2 = 13

as we can see, when we try it in our equations, x and y are interchangable : one has to be 9 and the other 13.

so, the older brother is 13 now.

User Joel Vroom
by
4.7k points